Rising concentrations of polybrominated diphenyl ethers (PBDEs) in Nigerian foodstuffs despite global restrictions - Yulong Ma; William A. Stubbings; Reginald Cline-Cole; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Emerging Contaminants, 2024)
The presence of brominated flame retardants (BFRs) in foodstuffs of African origin is poorly understood. To fill this gap, animal-derived food samples comprising 13 different items originally from Nigeria were obtained in 2021, and concentrations of novel brominated flame retardants (NBFRs), polybrominated diphenyl ethers (PBDEs), and hexabromocyclododecane (HBCDD) were measured. Arithmetic mean concentrations of NBFRs, PBDEs, and HBCDD in Nigerian foodstuffs were 2.1 ng/g (18 ng/g lipid weight (lw)), 1.3 ng/g (9.2 ng/g lw), and 0.42 ng/g (2.8 ng/g lw), with median concentrations of 1.7 ng/g (14 ng/g lw), 1.1 ng/g (8.2 ng/g lw), and <0.34 ng/g (<3.3 ng/g lw), respectively. Higher concentrations of NBFRs than of PBDEs and HBCDDs in Nigerian foodstuffs likely reflect use of NBFRs as substitutes for legacy BFRs in Nigeria. Comparison with previous dietary studies reveals rising concentrations of PBDEs in Nigerian foodstuffs in recent years with associated rises in dietary exposure, possibly due to active domestic use of PBDEs in Nigeria. Reassuringly, comparison of our exposure estimates with health-based limit values suggests adverse health effects of dietary intake of BFRs by Nigerians are unlikely to occur.